Money transfer from Ah Louis to Tony [Jack?] [Jun?], October 7, 1891 - Wells Fargo and Companies Express::::::::: (1891)
Ah Louis used the Wells, Fargo & Co's Express to send $20.00 to Tony [?] [Jun?] who lived in San Francisco. This service was to pay money by telegraph.